ORIGIN OF CONTRASTING FEATURES AND PRESERVATION PATHWAYS IN KEROGENS FROM THE KASHPIR OIL SHALES (UPPER JURASSIC, RUSSIAN PLATFORM) - Riboulleau A.; Derenne S.; Largeau C.; Baudin F. (My University, 2001)
A kerogen, termed aBS base, from the Gorodische section (Russian Platform) was studied using a combination of microscopic, spectroscopic and pyrolytic methods in order to determine its chemical structure, source organisms and formation pathway(s). This kerogen was mainly formed via degradation-recondensation of phytoplanktonic material. Selective preservation and natural sulphurisation pathways only played a minor role, whereas a substantial contribution of ether linked lipids was noticed, revealing large oxygen cross-linking. Such observations allowed us to put forward, for the first time to the best of our knowledge, a substantial role for the oxidative reticulation pathway in the formation of a kerogen. Comparision with a previously studied sample from the same outcrop revealed contrasting features which reflect differences in preservation pathways triggered by different depositional conditions.
Keywords: KASHPIR OIL SHALES; PYROLYSIS; FTIR; SOLID STATE 13C NMR; MELANOIDINS; OXYGEN CROSS-LINKING; PRESERVATION VIA OXIDATIVE RETICULATION